1997
DOI: 10.1039/a705829b
|View full text |Cite
|
Sign up to set email alerts
|

Telluroether adducts of tin(IV) halides: synthesis, spectroscopy and structures

Abstract: The extremely moisture-sensitive [SnX 4 (Me 2 Te) 2 ] and [SnX 4 (ditelluroether)] [X = Cl or Br;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 17 publications
8
80
0
Order By: Relevance
“…The Sn-P distances [2. [24]. The trans influence, manifested in the variation of the Sn-Cl bond lengths (Table 4), agrees well with the pattern found in most adducts of SnX 4 (X = Cl, Br, I) with soft donor ligands [2,27,[34][35][36]. As expected the P(1)-Sn(1)-P(2) bite angle [78.37 (2) [24].…”
Section: Crystal and Molecular Structuressupporting
confidence: 72%
“…The Sn-P distances [2. [24]. The trans influence, manifested in the variation of the Sn-Cl bond lengths (Table 4), agrees well with the pattern found in most adducts of SnX 4 (X = Cl, Br, I) with soft donor ligands [2,27,[34][35][36]. As expected the P(1)-Sn(1)-P(2) bite angle [78.37 (2) [24].…”
Section: Crystal and Molecular Structuressupporting
confidence: 72%
“…66) [339]. Air-stable ligands including Ph 2 PCH 2 PPh 2 , Ph 2 As(CH 2 ) 2 AsPh 2 and o-C 6 H 4 (PPh 2 ) 2 air-oxidise readily in the presence of bismuth(III) halides to form complexes of the corresponding ligand dioxides [335,340]. The reactions are slower than in the case of Sn(IV) or Ge(IV) halides (q.v.…”
Section: Arsenicmentioning
confidence: 99%
“…[335]. The structures of all the antimony halide complexes show varying degrees of distortion about the central antimony and a range of bond lengths, which seem to result from a number of factors [8,18].…”
Section: Arsenicmentioning
confidence: 99%
“…The Te-O distances are very long (2.329(4) Å; 2.471(4) Å), compared with a standard Te-O bond distance of 1.95 Å. [15] However, based on the clear difference in the 19 F NMR spectrum of purely ionic triflate, we concluded that the triflate substituents remain weakly associated with Waals radii (3.60 Å). This "pinwheel" bonding motif defined by the pyridine ligands has been observed in a number of transition metal species, but compound 9 is only the third p-block system isolated in such a bonding arrangement, and the sole example from Group 16.…”
Section: Figure 1 Examples Of Main Group Centered Dicationsmentioning
confidence: 83%
“…The Te-C distances in 10 (2.136(4), 2.138(3) Å) are consistent with single bonds as they display no shortening indicative of multiple bond character and are similar to other representative Te-C single bonds (≈ 2.10 Å). [10,19] This underscores the difference in structure from 12, in that 10 cannot be represented as an analogue of 12a, but is best drawn as a heavy element analogue of 12b ( Figure 5). …”
Section: Figure 1 Examples Of Main Group Centered Dicationsmentioning
confidence: 99%